An ultra-small NiFe2O4 hollow particle/graphene hybrid: fabrication and electromagnetic wave absorption property. Issue 6 (23rd January 2018) - Yan, Feng; Guo, Dong; Zhang, Shen; Li, Chunyan; Zhu, Chunling; Zhang, Xitian; Chen, Yujin
Abstract : Ultra-small NiFe2 O4 hollow particles, with the diameter and wall thickness of only 6 and 1.8 nm, respectively, were anchored on a graphene surface, showing an excellent electromagnetic wave absorption property. Abstract : Herein, ultra-small NiFe2 O4 hollow particles, with the diameter and wall thickness of only 6 and 1.8 nm, respectively, were anchored on a graphene surface based on the nanoscale Kirkendall effect. The hybrid exhibits an excellent electromagnetic wave absorption property, comparable or superior to that of most reported absorbers. Our strategy may open a way to grow ultra-small hollow particles on graphene for applications in many fields such as eletromagnetic wave absorption and energy storage and conversion.